The Impact of Peat Moss Amendments on the Microbial Load in Used Pine Shaving Poultry Litter - Everett, D.L.; Vizzier-Thaxton, Y.; McDaniel, C.D.; Kiess , A.S. (International Journal of Poultry Science, 2013)
In addition to pine shavings, alternative litter sources for poultry bedding include sand, pine straw, or even peat moss. Peat moss has a high absorptive capacity and is naturally acidic, possibly making it a good poultry litter amendment. The objective of this study was to determine if microbial populations changed when different levels of peat moss were added to poultry litter. Experimental treatments included 0, 13 and 20% peat moss which were added to used pine shavings. A total of 216 male broilers (42 d) were separated into 18 pens (6 pens/3 treatments). Control litter samples (100 g) were collected prior to the addition of peat moss and birds (0 d); then litter samples from each pen were collected weekly thereafter for 3 wk. From each litter sample, 10 g was diluted in 90 ml of Buttersfield’s Phosphate and then serially diluted. For Tryptic soy agar, MacConkey agar and Sabouraud Dextrose agar, 100 μl of inoculums was plated in duplicate to detect aerobic bacteria, total coliforms and yeasts/molds, respectively. Plates were incubated aerobically for 24 h at 37°C and then counted. The results indicated that there were no differences between treatments for total aerobic bacterial counts. Initially, an increase in coliforms was detected in treatments that had peat added. By the second week coliforms were reduced in the peat treatments and a treatment by week interaction was detected (P = 0.012). The level of coliforms in litter which had peat added (13 or 20%) was 3.92 and 4.04 log cfu/g, respectively. For the control litter where no peat was added, coliforms were 5.43 log cfu/g of litter. Also a treatment by week interaction was detected for yeast and molds (P = 0.0025). Over each week of the experiment a decrease in the number of yeast and molds occurred in litter where peat was added. In week 1, yeast and molds were at 5.22 log cfu/g of litter in the control and 4.42 and 4.54 log cfu/g of litter in the 13 and 20% peat treatments, respectively. Week 2 the yeast and molds were 5.43 log cfu/g of litter in the control and 4.0 and 3.88 log cfu/g of litter for the 13 and 20% peat treatments, respectively. For, week 3 the yeast and molds were 6.03 log cfu/g of litter in the control and 4.82 and 3.72 log cfu/g of litter for the 13 and 20% peat treatments, respectively. In conclusion, the data demonstrates that the addition of peat moss may be a useful amendment for reducing bacteria, yeasts and molds in poultry litter. Overall, future studies should test the absorptive capacity of peat moss for trapping ammonia and changing the litter pH which could demonstrate how peat moss is actually reducing bacteria and yeast/mold growth in poultry litter.